Determining the Optimum Addition of Vegetable Materials in Adobe Bricks. (2016) - Calatan, Gabriela; Hegyi, Andreea; Dico, Carmen; Mircea, Calin
Abstract: Housing construction technology using clay soil in various forms - paved, adobe bricks form or other - is already known and used since ancient times. Over the years, there have been numerous studies and research to improve this technology and to obtain more resistant, comfortable and durable structures. This paper presents an experimental study regarding the effectiveness of natural fiber disperse reinforcement in the adobe bricks. The results indicate an improved mechanical strength and a better thermal conductivity of the clay composite material. The variation of watched physical-mechanical parameters was influenced by the type of the used organic material, hemp fiber or straw, and of the amount entered in the mixture. By analyzing simultaneously all watched physical-mechanica parameters, for the used clay mixture, it was set an optimum addition of hemp fibers, as 9-10% percent by volume, respectively an optimal straw addition, 30-40% percent by volume.